Curable composition and method for producing same

A curable composition combining cyclic carbonate and calcium hydroxide provides rapid curing and high compressive strength, addressing the limitations of existing materials in achieving rapid solidification and structural integrity for construction and 3D printing.

JP7606375B2Active Publication Date: 2024-12-25MITSUBISHI UBE CEMENT CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021044909
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-18
Publication Date
2024-12-25
Estimated Expiration
2041-03-18

AI Technical Summary

Technical Problem

Existing curable compositions fail to achieve high compressive strength and curing speed, particularly in applications like 3D printing materials, where rapid solidification and robust structural integrity are required.

Method used

A curable composition is developed using a specific combination of cyclic carbonate, such as glycerol carbonate, and calcium hydroxide, which generates carbon dioxide upon mixing, filling gaps and forming a dense morphology, resulting in high compressive strength.

Benefits of technology

The composition achieves rapid curing and high compressive strength within 1.5 hours, with strengths exceeding 30N/mm², suitable for construction materials and 3D printing applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606375000011
    Figure 0007606375000011
  • Figure 0007606375000012
    Figure 0007606375000012
  • Figure 0007606375000001
    Figure 0007606375000001
Patent Text Reader

Abstract

To provide a method for producing a curable composition that can give a cured body of high strength at a high curing rate.SOLUTION: A curable composition contains a cyclic carbonate having a hydroxy group, calcium hydroxide, and aggregate. Within 1.5 hours just after mixing the cyclic carbonate with the calcium hydroxide, the compression strength of the curable composition becomes 30 N / mm2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition. [Background technology]

[0002] Patent Document 1 is an invention in the field of application of lumps called concretions found in layers of sedimentary rock. Patent Document 1 proposes a structural material that is characterized by comprising a base material for forming a structure, and an ion supply source that supplies at least one of cations and anions that constitute poorly soluble salts that are present inside or on the surface of the base material and have a solubility in water of a first value or less at the temperature of the environment in which the base material is disposed. Non-Patent Document 1 describes the principle of Patent Document 1.

[0003] Furthermore, an invention in the field of inorganic hardening compositions is disclosed in Patent Document 2. Patent Document 2 describes that a composition containing magnesium oxide, water, and ethylene carbonate (ethylene carbonate) is molded and cured for 28 days to obtain a building material with excellent compressive strength. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2020 / 040243 [Patent Document 2] Japanese Patent Application Publication No. 08-143352 [Non-patent literature]

[0005] [Non-Patent Document 1] Hidekazu Yoshida et al., Scientific Reports volume 5, Article number: 14123 (2015) Summary of the Invention [Problem to be solved by the invention]

[0006] Patent Document 1 describes the application of the mechanism by which spherical lumps called concretions are formed in horn shells to fields such as cement-based structural materials. The compressive strength of natural concretions is, for example, 100 N / mm 2 However, in the structure produced by the method described in Patent Document 1, although a layer of calcium carbonate could be formed, it was not possible to reproduce the high compressive strength of natural concretions.

[0007] Furthermore, for example, materials for modeling used in 3D printers are required to have not only high strength after hardening but also a high hardening speed.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a curable composition which has a high curing rate and is capable of giving a cured product with high strength. [Means for solving the problem]

[0009] The present inventors have investigated a method for producing a high-strength hardened body from a hardenable composition by applying the mechanism of concretions. As a result of observing natural concretions, the present inventors have found that calcium carbonate is arranged in the gaps between rocks, resulting in a morphology in which the components are densely packed. They then inferred that the dense morphology is the reason for the high compressive strength and other strengths.

[0010] The present inventors considered kneading a carbonate source such as ethylene carbonate, propylene carbonate, or glycerol carbonate with a calcium source such as calcium hydroxide or calcium oxide in order to fill the gaps in calcium carbonate and create a dense morphology. After kneading, the carbonate source decomposes to generate carbon dioxide, and the generated carbon dioxide is absorbed by calcium hydroxide or calcium oxide to fill the gaps in calcium carbonate, and they conducted an experiment based on this assumption. Initially, the present inventors tried a method of generating carbon dioxide by thermally decomposing and hydrolyzing ethylene carbonate. As a result, they discovered that when a specific combination of glycerol carbonate (glycerol-1,2-carbonate) and calcium hydroxide is kneaded, a hardenable composition and structure that can produce a hardened body with high strength can be obtained, and thus the present invention was completed.

[0011] The detailed mechanism by which the hardened body of the present embodiment has high strength has not been clarified. The inventors have arrived at the finding from experiments that high strength can be achieved when glycerol carbonate is used as the carbonic acid supply source and calcium hydroxide is used as the calcium supply source. For example, if calcium hydroxide is used as the calcium source, ethylene carbonate as the carbonic acid source, and calcium carbonate as the aggregate, the compressive strength of the structure will be 5 to 10 N / mm 2 This is presumably because the melting point of ethylene carbonate is 36°C, and it is solid at 25°C, so it simply solidifies by incorporating the surrounding substances, and no hardening reaction occurs. When kneading this ethylene carbonate, it is used after it has been liquefied in a hot water bath. Note that glycerol carbonate is liquid at 25°C, so there is no need to bathe in hot water. For example, when calcium oxide is used as a calcium source, glycerol carbonate is used as a carbonic acid source, and calcium carbonate is used as an aggregate, the compressive strength of the structure is 30 to 40 N / mm 2 When the structure was left exposed to air it turned to powder and disintegrated. For example, when calcium oxide was used as the calcium source, glycerol carbonate as the carbonic acid source, and calcium carbonate as the aggregate, the hardening reaction occurred in the same way as when glycerol carbonate was used. However, when the hardened body was stored in the air, it turned into powder and collapsed (a dusting-like phenomenon occurred).

[0012] When the present inventors considered the mechanism by which the strength of the cured body of the present embodiment is improved, they considered Patent Document 2 as a system similar to the cured body of the present embodiment. However, although Patent Document 2 describes a system using magnesium oxide, ethylene carbonate, and water, it does not describe the mechanism in detail. The present inventors also investigated a system in which calcium hydroxide or calcium oxide is used as a calcium supply source, ethylene carbonate is used as a carbonic acid supply source, and water is further added, with reference to Patent Document 2. Although it depends on the composition of the raw materials, it has been confirmed that although heat is generated, hardening does not progress from the surface, or even if hardened, the hardened body does not exhibit the same compressive strength as the hardened body of the present embodiment.

[0013] As described above, the inventors have discovered that by studying the application of the concretion mechanism, a hardened body with high strength can be obtained, and have completed the present invention.

[0014] That is, the curable composition of the present invention contains a cyclic carbonate having a hydroxyl group and calcium hydroxide, and the compressive strength of the curable composition reaches 30 N / mm within 1.5 hours after the cyclic carbonate and calcium hydroxide are mixed. 2 That is all.

[0015] The above mixing is preferably carried out under reduced pressure, at 5° C. or lower, and for a mixing time of 5 minutes to 1 hour.

[0016] The cyclic carbonate is preferably a compound represented by the following formula (I). [ka] (In formula (I), R 1 is a divalent hydrocarbon group containing 2 to 6 carbon atoms, at least one of the hydrogen atoms of the hydrocarbon group being substituted with a hydroxy group.

[0017] The hardenable composition of the present invention preferably further contains an aggregate.

[0018] The mixing ratio of the cyclic carbonate is preferably 40 parts by mass or less per 100 parts by mass of the total amount of calcium hydroxide and aggregate.

[0019] The mixing ratio of the calcium hydroxide is preferably 80 parts by mass or less per 100 parts by mass of the total amount of the calcium hydroxide and the aggregate. Effect of the Invention

[0020] According to the present invention, it is possible to provide a curable composition which has a high curing rate and is capable of giving a cured product with high strength. [Brief description of the drawings]

[0021] [Figure 1] 1 is a photograph of a test specimen of Example 1. [Diagram 2] 1 is a SEM photograph of a specimen of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The curable composition of the present embodiment contains a cyclic carbonate having a hydroxy group and calcium hydroxide, and the compressive strength of the curable composition is 30 N / mm within 1.5 hours from immediately after mixing the cyclic carbonate and calcium hydroxide. 2 Such a curable composition has a high curing rate and can give a cured product with high strength.

[0023] The compressive strength of the hardenable composition was 40 N / mm within 1.5 hours after mixing the cyclic carbonate and calcium hydroxide.2 More than 50N / mm is preferable. 2 More preferably, it is 60N / mm 2 More preferably, it is 70N / mm 2 More preferably, it is 80N / mm 2 In view of workability, it is preferable that high hardness is developed as quickly as possible.

[0024] The compressive strength of the hardenable composition was 30 N / mm within 1.0 hour after mixing the cyclic carbonate and calcium hydroxide. 2 More than 40N / mm is preferable. 2 More preferably, it is 50N / mm 2 More preferably, it is 60N / mm 2 More preferably, it is 70N / mm 2 More than 80N / mm is highly desirable. 2 This is particularly preferable. For example, when creating construction materials using a 3D printer, first the outer frame is formed from a material that hardens quickly, and then other materials are filled inside. Therefore, from the viewpoint of forming the construction material at high speed, it is preferable that hardness is quickly developed. It is also preferable that hardness is quickly developed from the viewpoint of being able to withstand the increased force applied to the outer frame when the material is filled inside.

[0025] The compressive strength of the hardenable composition was 30 N / mm within 0.5 hours after mixing the cyclic carbonate and calcium hydroxide. 2 More than 40N / mm is preferable. 2 More preferably, it is 50N / mm 2 More preferably, it is 60N / mm 2 More preferably, it is 70N / mm 2 More than 80N / mm is very desirable. 2This is particularly preferable. For example, when creating construction materials using a 3D printer, the outer frame is first formed from a material that hardens quickly, and then other materials are filled inside. Therefore, from the viewpoint of forming construction materials at high speed, it is preferable that hardness is quickly developed. Even if it is not used in a 3D printer, when it is used as a molding material, it is preferable from the viewpoint of reducing the time required for manufacturing products and improving mass productivity.

[0026] The hardenable composition of the present embodiment may optionally contain other components such as aggregates as raw materials in addition to the cyclic carbonate having a hydroxyl group and calcium hydroxide. Examples of the aggregates include calcium carbonate. When other components are added to the hardenable composition, the measurement of the change over time in the compressive strength of the hardenable composition can be started immediately after mixing the cyclic carbonate having a hydroxyl group, calcium hydroxide, and other components.

[0027] The raw materials are mixed until the cyclic carbonate having a hydroxyl group, calcium hydroxide, and other components such as aggregates added as necessary are mixed almost uniformly. That is, the point when each component of the hardenable composition is mixed almost uniformly is regarded as immediately after mixing, and is the starting point of time when measuring the change over time in the compressive strength of the hardenable composition. The mixing method may be appropriately changed depending on the viscosity of the components used, and may be performed, for example, under reduced pressure, at a temperature of -5°C or higher and 5°C or lower, and for a mixing time of 5 minutes to 1 hour. The mixing may be performed using a kneader described later.

[0028] The curable composition may be left to stand under conditions of, for example, 15 to 25° C. (preferably 20° C.) and a relative humidity of 50 to 80% (preferably 60%) from immediately after the raw materials are mixed to prepare the curable composition until the compressive strength is measured. The compressive strength of the curable composition may be, for example, the compressive strength measured on a test specimen obtained by molding the composition by packing it into a formwork having a width of 1 cm, a depth of 1 cm, and a length of 6 cm.

[0029] (Method of producing curable composition) Hereinafter, a method for producing the curable composition according to the present embodiment and a method for producing the cured product will be described. The method for producing the curable composition according to the present embodiment includes a mixing step of mixing a cyclic carbonate having a hydroxyl group with calcium hydroxide to prepare a curable composition. In this specification, when "~" is used to indicate a numerical range, the endpoints of the numerical range are included.

[0030] <Mixing process> In the mixing step, the cyclic carbonate having a hydroxyl group and calcium hydroxide are mixed to produce a curable composition. When raw materials other than the cyclic carbonate having a hydroxyl group and calcium hydroxide are used, they are mixed together in the mixing step. The mixing method is not limited, and examples thereof include mixing using a batch type kneader such as a mixer, kneader, or kneader ruder, or a continuous type kneader such as an extruder equipped with a vent port and a vacuum chamber. In addition, in a system where hardening is unlikely to occur during mixing and there is no need to use a machine, the materials may be stirred by hand. As a method of mixing, for example, it is preferable to use a kneader equipped with a vacuum chamber. As an example of a kneader, for example, PNV-1T (motor: 100V250W, capacity: 1L, rotation speed: 28.8rpm to 62.4rpm, blade shape: Σ type) manufactured by Irie Shokai Co., Ltd., is exemplified. The better the dispersibility of the raw materials, the higher the compressive strength of the hardened body produced tends to be. On the other hand, hardening may progress along with the mixing of the raw materials. As a result, a kneader with a high shear stress that can improve the dispersibility of the raw materials even when hardening begins to progress is preferable.

[0031] In the mixing step, when there are multiple raw materials to be mixed, it is preferable to first mix powders with each other and liquids with each other, and then mix the powder mixture and the liquid mixture. This can further improve the dispersibility. For example, in a system in which glycerol carbonate, calcium hydroxide, and calcium carbonate (aggregate) are mixed, it is preferable to first mix calcium hydroxide and calcium carbonate to prepare a powder mixture, and then mix glycerol carbonate with the powder mixture.

[0032] In the mixing step, for example, it is preferable to remove moisture before mixing the raw materials, which can suppress hardening during mixing and allow a structure having a desired shape to be formed. Examples of the method of mixing after removing moisture include a method of mixing under reduced pressure, a method of mixing together with a moisture absorbent, a method of mixing in an environment where a moisture absorbent is placed, and a method of mixing while drying by heating. Examples of the method of mixing after removing moisture include mixing under reduced pressure, and more preferably mixing by drawing a vacuum. This allows kneading in a system with less moisture. The method for reducing the pressure is not limited, and for example, an oil rotary pump, an aspirator, a water seal pump, a rotary pump, or the like can be used. It is preferable to completely remove moisture, but in the actual manufacturing process, complete removal is difficult, and the inclusion of a small amount of moisture is permissible.

[0033] In the mixing step, for example, it is preferable to mix the raw materials while cooling. This makes it possible to suppress hardening during mixing, and to form a structure of a desired shape. The cooling temperature is not limited, but may be, for example, -50°C or higher, preferably -30°C or higher, more preferably -20°C or higher, even more preferably -10°C or higher, even more preferably 0°C or higher, and especially preferably 5°C or higher. The cooling temperature may be, for example, 25°C or lower, 20°C or lower, or 10°C or lower. The cooling method is not limited, but may be, for example, a method of cooling the kneading machine itself, such as a kneader.

[0034] The phenomenon that occurs in the mixing process will be explained. When the raw materials are mixed, for example, at low temperature and under reduced pressure, granulation occurs in which the particles gradually become larger. If mixing is continued after that, the granulated powder suddenly produces liquid on the surface, and a paste-like hardenable composition is formed. If this paste-like hardenable composition is filled into a mold and left in the air, it becomes a hardened product. For example, cooling the device to -5°C and evacuating in an environment with a temperature of 23°C and humidity of 60% will result in finer granulation during mixing (it is assumed that a small amount of air will be mixed into the device). Also, for example, cooling the device to -5°C and evacuating in an environment with a temperature of 5°C and humidity of 45% will result in finer granulation during mixing than the above-mentioned system.

[0035] Regarding the hardening composition according to the present embodiment, the mechanism by which the hardening reaction proceeds is unclear in many respects. One possibility is that glycerol carbonate is uniformly attached to the surfaces of calcium hydroxide and aggregate particles. When the curable composition having the preferred composition according to the present embodiment is kneaded, the powder particles are initially observed to grow larger (i.e., granulated). On the other hand, as the kneading is continued, light reflection is observed on the surface, as if the powder were wet. Next, the powder becomes paste-like, becoming a curable composition. This curable composition is then subjected to a molding process. The reason why the properties of the kneaded state change in this way is unclear. One possibility is that some kind of chemical reaction occurs due to shear heat, causing granulation. This suggests the possibility that, for example, carbon dioxide is produced from glycerol carbonate, which is absorbed by slaked lime to produce calcium carbonate, acting as a binder between the calcium hydroxide and aggregate. Alternatively, it is also suggested that, rather than a chemical reaction occurring, glycerol carbonate is well dispersed on the surfaces of the calcium hydroxide and aggregate, acting as a binder between the calcium hydroxide and aggregate.

[0036] <Forming process> The method for producing a cured product according to the present embodiment may further include a molding step of molding the curable composition into a desired shape to obtain a molded product after the mixing step described above. This allows a structure made of a cured product having a predetermined shape to be obtained.

[0037] For example, when glycerol carbonate and calcium hydroxide are mixed in the mixing step, if the mixture is left in air at room temperature, heat is generated immediately and hardening proceeds. Although the detailed mechanism is not clear, during hardening, calcium hydroxide absorbs carbon dioxide to become calcium carbonate, which fills the gaps between the raw materials such as calcium hydroxide. This makes it difficult to mold the composition into any shape after hardening. The hardenable composition is preferably molded into a desired shape by putting it into a mold such as a metal mold or a wooden frame.

[0038] <Drying process> The method for producing a cured body according to the present embodiment may further include a drying step for drying the cured body, if necessary. The temperature condition of the drying step is not limited, and may be, for example, 60°C or more, 80°C or more, or 100°C or more. The drying time may be, for example, 1 hour or more, 10 hours or more, 24 hours or more, or 72 hours or more. The drying step may be performed under reduced pressure. Depending on the formulation, a glycerin-like liquid may seep out from the hardened product, but this can be removed by a drying process. Cyclic carbonates also have the property of generating carbon dioxide through thermal decomposition. In addition, the case where the drying step is not performed is preferable from the viewpoint of improving toughness compared to the case where the drying step is performed. Drying may be performed, for example, by heating with a heater or by heating with hot air.

[0039] In addition to the above-mentioned drying process, the cured composition may be cured. For example, the curing may be performed by steam curing under high temperature moisture, or the cured composition may be submerged in hot water. For example, when the cured composition is submerged in hot water at 100°C, the curing proceeds and the composition turns white.

[0040] <Curing process> The method for producing a cured product according to the present embodiment includes a curing step of curing the curable composition or the molded product. The curable composition according to the present embodiment often has a high curing rate, and often cures simply by leaving it at ambient temperature (about 15 to 35°C, 20°C, 25°C, etc.) without heating, but may be heated to further increase the curing rate. The heating temperature is not particularly limited, but may be 110°C or lower, or may be 90 to 100°C. In addition, if the reaction heat during curing is a problem depending on the embodiment, curing may be performed while cooling. The humidity (relative humidity, RH) during the curing step is not particularly limited, but may be, for example, 30 to 80%. The curing step may be performed after the drying step or simultaneously with the drying step (i.e., a step of curing while drying).

[0041] <Raw materials> Next, the raw materials of the curable composition according to this embodiment will be described. The raw materials used are essentially a cyclic carbonate having a hydroxyl group and calcium hydroxide.

[0042] (Cyclic carbonates having hydroxy groups) The cyclic carbonate having a hydroxyl group may be, for example, one that generates carbon dioxide after mixing, and is preferably one that generates carbon dioxide by reacting with other raw material components. The size of the ring of the cyclic carbonate having a hydroxyl group may be, for example, an 8-membered ring or less, preferably a 7-membered ring or less, and more preferably a 6-membered ring or less. The size of the ring of the cyclic carbonate having a hydroxyl group may be, for example, a 4-membered ring or more, and preferably a 5-membered ring or more. This allows stable generation of carbon dioxide during mixing. Specifically, the compound represented by the following formula (I) can be mentioned. [ka] (In formula (I), R 1is a divalent hydrocarbon group having 2 to 6 carbon atoms, and at least one of the hydrogen atoms of the divalent hydrocarbon group is substituted with a hydroxy group.

[0043] R 1 R is preferably a divalent hydrocarbon group having 3 to 5 carbon atoms. The number of hydroxy groups in the cyclic carbonate is preferably 1 to 3, and more preferably 1 or 2. 1 may contain a carbon-carbon double bond (i.e., it may be an unsaturated hydrocarbon group).

[0044] It is preferable that the cyclic carbonate contains at least one of the compounds represented by the following formula (II) or (III). [ka] (In formula (II), R 11 and R 12 are each independently a hydrogen atom, a hydroxyl group, or a -CHOH group; in formula (III), R 21 , R 22 and R 23 are each independently a hydrogen atom, a hydroxyl group, or a -CHOH group.

[0045] R 11 and R 12 are preferably each independently a hydrogen atom or a -CHOH group. 21 and R 23 are preferably each independently a hydrogen atom or a -CHOH group.

[0046] The compounds represented by formula (II) and (III) include the following compounds (IIa) to (IIh) and (IIIa) to (IIId). [ka] [ka]

[0047] Among these, glycerol carbonate (a compound of formula (IIa), glycerol 1,2-carbonate) or a compound of formula (IIIb) (glycerol 1,3-carbonate) is preferred, and glycerol carbonate is more preferred. Glycerol carbonate is preferred from the viewpoint of reacting with calcium hydroxide at room temperature.

[0048] Glycerol carbonate may contain glycerin and other components as impurities.

[0049] (Calcium hydroxide) There is no limitation on the calcium hydroxide, and it may be a natural or synthetic product, and a commercially available product may also be used. An example of commercially available calcium hydroxide is special slaked lime grade manufactured by Ube Material Industries, Ltd. In addition, a product in which calcium hydroxide and calcium carbonate are mixed in advance may also be used, and an example of such a product is a fertilizer grade product manufactured by Tagawa Lime Industries, Ltd.

[0050] The amount of the cyclic carbonate having a hydroxyl group added (charge amount, i.e., mixing ratio) is, for example, preferably 100 parts by mass or less, more preferably 70 parts by mass or less, more preferably 65 parts by mass or less, even more preferably 60 parts by mass or less, and even more preferably 55 parts by mass or less, relative to 100 parts by mass of calcium hydroxide. The amount of the cyclic carbonate having a hydroxyl group added is, for example, preferably 30 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 45 parts by mass or more, even more preferably 48 parts by mass or more, and even more preferably 50 parts by mass or more, relative to 100 parts by mass of calcium hydroxide. It is presumed that by controlling the amount of the cyclic carbonate having a hydroxyl group added within the above range, the carbon dioxide generated from the cyclic carbonate having a hydroxyl group can be appropriately absorbed by the calcium hydroxide, which allows the gaps in the calcium hydroxide, etc. to be filled with calcium carbonate, thereby further improving the compressive strength.

[0051] (aggregate) In addition to the raw materials, cyclic carbonate having a hydroxyl group and calcium hydroxide, for example, it is preferable to further add aggregate. As the aggregate, calcium carbonate is preferable. The calcium carbonate may be a natural product or a synthetic product, and a commercially available product may also be used. As a commercially available calcium carbonate, road grade manufactured by Ube Material Industries, Ltd. may be mentioned.

[0052] When aggregate is added, the amount of cyclic carbonate having a hydroxyl group added (charge amount, i.e., mixing ratio) is, for example, preferably 100 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 40 parts by mass or less, and especially preferably 32 parts by mass or less, relative to 100 parts by mass of calcium hydroxide and aggregate in total, from the viewpoint of ease of mixing and dispersibility of the curable composition, for example, the amount of cyclic carbonate having a hydroxyl group added is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 25 parts by mass or more, and especially preferably 28 parts by mass or more, relative to 100 parts by mass of calcium hydroxide and aggregate in total. Although the detailed mechanism is unclear, it has been confirmed that, when calcium hydroxide and aggregate are added, the smaller the amount of cyclic carbonate having a hydroxyl group added, the easier it is to improve the strength. By setting the amount of cyclic carbonate to be added within the above range, the mixing step can be carried out smoothly, and furthermore, maintaining a balance that allows the amount of cyclic carbonate having a hydroxyl group to be reduced is important in order to obtain high strength.

[0053] When aggregate is added, the amount of calcium hydroxide added (charge amount, i.e., mixing ratio) is, for example, preferably 80 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 65 parts by mass or less, even more preferably 63 parts by mass or less, very preferably 50 parts by mass or less, and particularly preferably 40 parts by mass or less, relative to 100 parts by mass of the total of calcium hydroxide and aggregate. The amount of calcium hydroxide added is, for example, preferably 20 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 40 parts by mass or more, even more preferably 50 parts by mass or more, and particularly preferably 55 parts by mass or more, relative to 100 parts by mass of the total of calcium hydroxide and aggregate. It is considered important that calcium hydroxide absorbs carbon dioxide and becomes calcium carbonate in order to achieve high strength. In addition, when the amount of calcium hydroxide added is 20 parts by mass or more, the expansion of the hardened body can be prevented, and the strength is improved. For this reason, it is preferable that the amount of calcium hydroxide added is within the above numerical range.

[0054] (Water reducing agent) The raw material may further contain a water reducing agent. This allows the mixing step to be performed while reducing the amount of cyclic carbonate having a hydroxyl group added. The type of water reducing agent is not limited, but examples that can be used include nitrohumate, lignin sulfonate, citric acid, polycarboxylic acid, and naphthalene.

[0055] (Other ingredients) The raw material may further contain a carbonate ester (excluding cyclic carbonates having a hydroxyl group) as another component. Examples of the carbonate ester include ethylene carbonate, propylene carbonate, 1,3-dioxane-2-one, 4-fluoro-1,3-dioxolan-2-one, 4-chloro-1,3-dioxolan-2-one, 4-vinyl-1,3-dioxolan-2-one, 4-methoxy-1,3-dioxolan-2-one, and vinylene carbonate. The raw material may also contain, as other components, for example, a small amount of alcohol, which can promote ring-opening of the cyclic carbonate having a hydroxyl group.

[0056] The hardened body of this embodiment is obtained by hardening the hardenable composition. As described later, the hardened body of this embodiment contains calcium carbonate produced by the reaction of calcium hydroxide with carbon dioxide, and may contain unreacted calcium hydroxide. In addition, when the hardenable composition contains aggregate, the hardened body also contains the aggregate. That is, the hardened body of this embodiment can be said to be a bonded body in which particles containing calcium carbonate and, optionally, calcium hydroxide or aggregate are bonded. Each particle contained in the hardened body may contain one or more of calcium carbonate, calcium hydroxide, and aggregate. The hardened body of this embodiment may be a structure formed into a predetermined shape in advance, or may not be formed.

[0057] <Structure> Next, the structure according to this embodiment will be described. The structure according to this embodiment is obtained by molding and curing the curable composition.

[0058] (Inorganic component) When the structure is subjected to wide-angle X-ray diffraction measurement to analyze the inorganic components, the content of calcium carbonate in the structure is preferably 5 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 40 parts by mass or more, and even more preferably 60 parts by mass or more, relative to 100 parts by mass of calcium carbonate and calcium hydroxide in total. This can improve the strength of the structure. The content of calcium carbonate in the structure may be 100 parts by mass or less, 99 parts by mass or less, or 90 parts by mass or less.

[0059] The particle size of calcium hydroxide and calcium carbonate in the structure is preferably 5 μm or more, more preferably 6 μm or more, more preferably 7 μm or more, and even more preferably 10 μm or more. This makes it possible to reduce the surface area of ​​the interface of the inorganic particles per unit volume. This reduces the frequency of defects and improves the strength of the structure. The particle size of the inorganic components constituting the structure can be measured, for example, by the following method. First, the structure is broken to prepare a cross section. Next, a 3000x photograph is taken with a SEM (Scanning Electron Microscope). Next, for each particle shown in the photograph, the length in the longest direction is taken as the particle size (hereinafter also referred to as the maximum particle size).

[0060] In the hardened body, the elemental concentration of calcium is preferably 20 to 70 atomic %, more preferably 25 to 65 atomic %, and even more preferably 30 to 60 atomic %. In addition, in the hardened body, the elemental concentration of carbon is preferably 20 to 80 atomic %, more preferably 30 to 70 atomic %, and even more preferably 40 to 65 atomic %. When the elemental concentrations of calcium and carbon are each within the above ranges, the compressive strength of the hardened body tends to be superior. The concentration of each element in the hardened body can be measured, for example, by energy dispersive X-ray analysis.

[0061] (organic ingredients) In the curable composition, it is believed that cyclic carbonates having hydroxyl groups undergo ring-opening polymerization addition and decarboxylation reactions to generate carbon dioxide. In general, cyclic carbonate compounds undergo ring-opening by nucleophilic substitution reactions at the carbonyl carbon with nucleophiles. The reaction of ethylene carbonate with nucleophile ZOH having an -OH moiety is shown below as an example. [ka] In the formula, ZOH represents a nucleophile having an OH moiety. Z may be an organic group (for example, when ZOH is an alcohol) or a hydrogen atom (i.e., when ZOH is water). It is known that such a reaction is accelerated in the presence of a base catalyst. The curable composition of the present embodiment contains calcium hydroxide, which is highly basic, and the aggregate may also have basicity, so it is believed that these function as a catalyst. In the curable composition, it is considered that the hydroxy group of the cyclic carbonate compound having a hydroxy group, water that may be contained as an impurity, alcohol, and the above-mentioned nucleophile function. In addition, since the product of the above-mentioned ring-opening addition reaction also has a hydroxy group, it can function as a nucleophile to the cyclic carbonate having a hydroxy group. In this case, it is considered that the ring-opening addition reaction proceeds sequentially, and a compound (polymer or oligomer) that has undergone ring-opening addition polymerization can be produced. In the above chemical reaction formula, ZOH is OH - In this case, the reaction product reacts with water to cause a decarboxylation reaction (hydrolysis reaction of the cyclic carbonate compound). During this reaction, alcohol (glycerin in the case of glycerol carbonate) is produced (hydrolysis reaction). Moreover, carbonate compounds are generally known to undergo a decarboxylation reaction as follows. [ka] Therefore, in the polymer or oligomer produced by the ring-opening addition polymerization, a part or all of the carbonate groups (-OC(=O)-O-) of these molecules undergo a decarboxylation reaction and are replaced with ether bonds (hydroxy groups in the case of terminal carbonate groups). It is considered that the organic components may also include high molecular weight components produced in this way. It is believed that at least a part of the carbon dioxide produced in the series of reactions reacts with calcium hydroxide to produce calcium carbonate. That is, in the curable composition, the cyclic carbonate compound having a hydroxyl group functions as a carbonic acid supply source, and calcium hydroxide functions as a calcium supply source. It is believed that the calcium carbonate phases that grow at this time are intricately bonded (adhered) to each other while involving the surrounding calcium hydroxide in the middle of reaction, aggregates, etc., to form a strong bond.

[0062] For example, when glycerol carbonate is used, it is believed that a substance represented by the following formula (1) is produced by ring-opening addition polymerization. [ka] (In the formula (1), R is any one of the following formulas (2): [ka]

[0063] It is also believed that cyclic carbonates having hydroxyl groups are hydrolyzed to generate carbon dioxide even in the structure (hardened body). For example, as described above, glycerol carbonate is hydrolyzed to generate glycerin and carbon dioxide.

[0064] (density) The apparent density of the structure according to this embodiment is, for example, 3.0 g / m 3 Less than or equal to 2.7 g / m 3 It is preferable that the content is 2.5 g / m or less. 3 More preferably, it is 2.3 g / m or less. 3 The structure according to the present embodiment can achieve both low density and high strength, which cannot be achieved with existing materials. As a result, the structure according to the present embodiment is also preferable as a building material, for example.

[0065] <Application> The curable composition can be used, for example, as a material for a 3D printer. The curable composition of the present embodiment has excellent modeling properties using a 3D printer from the viewpoints of the curing speed after mixing and the strength after curing. In addition, the hardenable composition or the hardened body can be used, for example, to absorb carbon dioxide (carbon dioxide absorbent) since unreacted calcium hydroxide contained in a structure can adsorb and remove carbon dioxide in the atmosphere. The hardened body according to this embodiment can be suitably used as a carbon dioxide absorption material with excellent strength. Using such a material as a substitute for cement and concrete can contribute to the realization of a low-carbon society. Furthermore, the structure according to the present embodiment can be used, for example, as an alternative material to fiber-reinforced concrete. The structure according to the present embodiment is preferable in that it does not contain materials that are difficult to process, such as metal fibers, and can achieve high strength.

[0066] <Other uses> The cured product of the present embodiment may be obtained by curing the curable composition without going through a molding step. Examples of applications of such a curable composition include injection materials and coating agents.

[0067] The present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention.

[0068] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES

[0069] The present invention will be described in detail below using examples, but the present invention is not limited to the descriptions of these examples. Details of the components used in each of the Examples and Comparative Examples are given below.

[0070] (raw materials) Glycerol carbonate (hereinafter referred to as GC. 90% purity, the remaining 10% is glycerin, glycerol carbonate whose hydroxyl groups are converted to methyl carbonate) (Things that were done) ·Calcium hydroxide ·Calcium carbonate

[0071] <Method of producing curable composition> First, the curable compositions of Example 1 and Comparative Example 1 and the raw materials for the structures were prepared according to the compositions shown in Table 1.

[0072] (Mixing process) A mixing step then took place. In Example 1 and Comparative Example 1, since the shear stress required for mixing was large, mixing was performed using a kneader capable of cooling and decompression (manufactured by Irie Shokai Co., Ltd., grade: PNV-1T (motor: 100V250W, capacity: 1L, rotation speed: 28.8 rpm to 62.4 rpm, blade shape: Σ type)). The cooling temperature of the kneader was set to 5°C. After the raw materials were charged into the kneader, mixing was performed while drawing a vacuum using a vacuum pump. Mixing was performed for 15 to 20 minutes. As a result, a curable composition was obtained.

[0073] (molding process) Next, a molding step was carried out. Molding was performed by filling the curable composition into a mold having a width of 1 cm, a depth of 1 cm, and a length of 6 cm. The curable composition was left to stand in the mold under conditions of 20°C and a relative humidity of 60%. After molding in this manner, the curable composition was demolded to obtain a specimen (structure) of Example 1. The specimen of Example 1 is shown in FIG. 1. The specimen of Example 1 was subjected to measurements of compressive strength, apparent density, SEM observation, and XRD measurement. Each measurement method is described below. The compressive strength was measured 0.5 hours and 1.5 hours after the preparation of the curable composition (immediately after mixing the raw materials), and measurements other than the compressive strength were performed 3 hours after filling the formwork. The curable composition of Comparative Example 1 was not sufficiently cured even after 1.5 hours had passed since mixing, and therefore could not be demolded, making it impossible to measure the compressive strength and the like.

[0074] <Compressive strength> The compressive strength was measured according to the method described in JIS R5201:1997 (Physical test methods for cement). The evaluation results are shown in Table 1. It was confirmed that the curable composition of Example 1 already exhibited a high compressive strength at 0.5 hours after mixing.

[0075] <Apparent density> For the specimens of Example 1 molded into a size of 1 cm in width × 1 cm in depth × 6 cm in length, the mass of each specimen was measured at 3 hours of age, and the apparent density was calculated by dividing the mass by the volume of the molded body. As a result, the apparent density of all specimens was in the range of 2.1 g / cm 3 ~2.2 g / cm 3 As can be seen from this result, it was confirmed that the specimens of Example 1 are materials with low density and high strength.

[0076] <SEM observation> For the specimens of Example 1, SEM observation of the specimen cross-section was performed. The observation was carried out using Miniscope TM3030 (manufactured by Hitachi High-Technologies Corporation) under the conditions of a measurement magnification of 3000 times and a voltage of 15.0 kV. Also, Figure 2 is an SEM photograph of the specimen of Example 1. On the other hand, it was confirmed that Example 5 contains a large number of particles with a maximum particle size of 5.6 μm or more. Also, for the specimens of Example 1, EDX (Energy dispersive X-ray spectroscopy) measurement was performed at the black dot (●) portions in the SEM photograph of Figure 2. As a result, carbon and calcium were detected in the specimens of Example 1.

[0077] <XRD measurement> Each specimen of Example 1 was subjected to wide-angle XRD (X-ray diffraction: X-ray diffraction, device: D2 PHASER 2nd Generation (Bruker), CuKα ray) measurement. The diffraction pattern identified in the XRD measurement was peak-separated into a peak derived from CaCO3 crystals and a peak derived from Ca(OH)2, and the ratio was calculated. The abundance ratio of calcium carbonate and calcium hydroxide in the inorganic material is shown in Table 1. This confirmed the presence of unreacted calcium hydroxide in the specimen of Example 1. This provided each specimen with room for absorbing carbon dioxide. It was also confirmed that the higher the abundance ratio of calcium carbonate in the inorganic material, the higher the compressive strength. The abundance ratio based on the diffraction intensity of XRD reflects the abundance ratio of electrons, that is, the mass ratio.

[0078] [Table 1]

Claims

1. A hardenable composition comprising glycerol-1,2-carbonate, calcium hydroxide, and an aggregate, The mixing ratio of the glycerol-1,2-carbonate is 40 to 60 parts by mass per 100 parts by mass of the calcium hydroxide, and 20 to 40 parts by mass per 100 parts by mass of the calcium hydroxide and the aggregate, The mixing ratio of the calcium hydroxide is: 50 to 70 parts by mass per 100 parts by mass of the calcium hydroxide and the aggregate, The compressive strength of the hardenable composition is 30 N / mm within 1.5 hours from immediately after mixing the glycerol-1,2-carbonate, the calcium hydroxide, and the aggregate. 2 The above is the curable composition.

2. The hardenable composition described in claim 1, wherein the aggregate is calcium carbonate.

3. A method for producing a mixture comprising a mixing step of mixing glycerol-1,2-carbonate, calcium hydroxide, and aggregate, In the mixing step, The mixing ratio of the glycerol-1,2-carbonate is 40 to 60 parts by mass per 100 parts by mass of the calcium hydroxide, and 20 to 40 parts by mass per 100 parts by mass of the calcium hydroxide and the aggregate, The mixing ratio of the calcium hydroxide is: 50 to 70 parts by mass per 100 parts by mass of the calcium hydroxide and the aggregate, In the mixing step, mixing is carried out under reduced pressure, at 5° C. or lower, and for a mixing time of 5 minutes to 1 hour; The method for producing a hardenable composition, wherein the compressive strength of the hardenable composition becomes 30 N / mm 2 or more within 1.5 hours immediately after mixing the glycerol-1,2-carbonate, the calcium hydroxide, and the aggregate.

4. A method for producing a hardenable composition as described in claim 3, wherein the aggregate is calcium carbonate.

Citation Information

Patent Citations

  • Method of concreting ground

    JP1979028407A

  • Carbonated cured material

    JP1989270552A

  • Inorganic curing composition

    JP1995126048A

  • Production of inorganic curable composition

    JP1996143352A

  • A thermoplastic powder material system for forming appearance models from 3d printing systems

    JP2007502713A